Antibiotics prescribing habits of Brazilian general dental practitioners during periodontal treatments - Ceribelli, Ariane Oliveira; Alves, Brenda Stephanie Batista; Tajima, Thais Marques Do Nascimento; Martins, Christine Men; Batista, Victor Eduardo de Souza [UNESP]; Santinoni, Carolina Dos Santos [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: Periodontal treatment involves procedures aimed to reduce bacterial load, involving or not the use of local or systemic antibiotics. Objective: The purpose of this study was to assess Brazilian dentists’ knowledge about antibiotics prescription during periodontal treatment. Material and method: An online questionnaire was available asking for systemic application of local or systemic antibiotics prescription (frequency, and sequence with mechanical periodontal treatment) and in relation to different periodontal diseases. The use of microbial diagnostic services and volunteers’ demographic data were also elucidated. Data were statistically analyzed (Binomial Test, p<0.05). Result: Three hundred and ninety-three volunteers answered the questionnaire. Twenty-three percent males and 76.2% females. Average age was 27.7 years. Minority (19.2%) of the volunteers reported to indicate systemic antibiotics to treat gingivitis or periodontitis stages I and II (old slight and moderate chronic periodontitis). Majority of the professionals indicate it to treat periodontal abscess, necrotizing ulcerative gingivitis or periodontitis, periodontitis in severe immunodeficiencies, old aggressive periodontitis, and periodontitis stages III and IV (old severe chronic periodontitis). Rarely (2.5%) the prescription was without the combination with mechanical therapy. Microbiological tests as an auxiliary diagnostic method are rarely (3.1%) requested due to lack of information or cost. Most frequent answers about the number of times professionals reported prescribing systemic antibiotics as part of periodontal treatment per trimester was “at least once”, followed by “2 times”. Conclusion: It can be concluded that Brazilian dentists have knowledge about the correct prescription of antibiotics in periodontal therapy.
Hábitos de prescrição de antibióticos de dentistas brasileiros durante tratamentos periodontais
Keywords: antibiotics; Dentistry; periodontics; questionnaire